Perbedaan Motivasi Siswa Usia 6-12 tahun dalam Upaya Pencegahan Tuberkulosis Paru di Daerah Prevalensi Tinggi dan Prevalensi Rendah di Kabupaten Jember (The Difference Levels of Motivation in 6-12 years-old Students Regarding Pulmonary Tuberculosis Prev - Risha Putri Mahardika; Latifa Aini Susumaningrum; Wantiyah Wantiyah (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Pulmonary tuberculosis control is one of important aspect to decrease mortality in children. One of factors that influence health behaviors to prevent tuberculosis is motivation. This research aimed to analyze the difference levels of motivation in 6-12 year-old students regarding pulmonary tuberculosis preventions between high and low prevalence area at Jember. This research used comparative analytical study with cross sectional design. The subjects of this study were students aged 6-12 years old in elementary schools that located in high and low prevalence area. Samples were obtained by probability sampling technique with multistage random sampling revealed 129 students in high prevalence area and 107 students in low prevalence area. The data were gained by using questionnaire and analyzed by Mann Whitney with CI=95% and α=0,05. The results showed that in both areas more than half students had high motivation; 71 respondents (55%) in high prevalence area, and 71 respondents (66.4%) in low prevalence area. Furthermore, the result showed that there were difference levels of motivation in students aged 6-12 year-old regarding pulmonary tuberculosis preventions between high and low prevalence area at Jember (p value=0,000). Overall, every health care setting should give health education to improve public motivation in preventing pulmonary tuberculosis. Keywords: tuberculosis prevention, motivation, high prevalence, low prevalence